Programma: 27 oktober Herman Brood birthday party; 28 oktober Soirée Sénégalaise; 29 oktober Supernovas goes Dutch; 30 oktober Paradise; 31 oktober Peter Hammill
Programma: 27 oktober Herman Brood birthday party; 28 oktober Soirée Sénégalaise; 29 oktober Supernovas goes Dutch; 30 oktober Paradise; 31 oktober Peter Hammill.